Caracterização de uma β-1,4-glucanase da família GH16 de Chromobacterium violaceum com atividade antifúngica contra Phytophthora infestans - Vieira, Filipe de Abreu (2023)
β-glucanases are glycoside hydrolases capable of degrading β-glucans into oligomers of high and low molecular weight. These enzymes are widely distributed across all domains of living beings, being classified into two categories based on catalytic patterns and substrate specificities, exo- and endo-β-glucanases. There is evidence that β-glucanases have activity against phytopathogens and can be used in plant breeding. Thus, it is necessary to produce these enzymes in a reproducible, environmentally sustainable way, in high concentrations and at low cost. A β-1,4-glucanase (CvCel96) from Chromobacterium violaceum ATCC 12472 was produced in Escherichia coli BL21(DE3) as a fusion protein with thioredoxin A, purified and characterized. The in silico analysis of the primary structure of the enzyme showed that it belongs to the family of glycoside hydrolases 16 (GH16), with a structure rich in β strands and catalytic residues Glu122, Asp124 and Glu126. Although GH16 family members with this structure are concomitant β-1,3-glucanases or β-1,3-1,4-glucanases, molecular docking analyzes have shown that CvCel96 has ancestral characteristics shared with cellulases of the GH7 family exhibiting interactions with tetracellulose. The purified recombinant protein exhibited a molecular mass of 40 kDa, when analyzed by SDS-PAGE, its identity was confirmed by mass spectrometry and its obtaining in native form was confirmed by circular dichroism spectra. Experimental analyzes showed the affinity of the enzyme for substrates of crystalline cellulose, showing the ability to hydrolyze avicel and filter paper. CvCel96 was able to inhibit the in vitro mycelial growth of Phytophthora infestans, an oomycete that has a cell wall rich in cellulose and causes late blight, a disease that affects several agricultural crops worldwide. CvCel96 was able to unwind the mycelium and induce morphological changes in the hyphae, such as cell wall desquamation observed by scanning electron microscopy. Thus, CvCel96 was characterized as a cellulase with potential application in the control of Phytophthora infestans that cause important diseases in agricultural crops.